L-3,4-Dihydroxyphenylalanine Recovers Circadian Rhythm Disturbances in the Rat Models of Parkinson's Disease by Regulating the D1R-ERK1/2-mTOR Pathway - Yang, Shuyuan; Wan, Ying; Wu, Na; Song, Lu; Liu, Zhihua; Zhao, Jiahao; Liu, Ying; Liu, Zhenguo; Gan, Jing (Frontiers in Aging Neuroscience, 2021)
Objective: Patients with Parkinson's disease (PD) frequently experience disruptions in the 24-h daily profile of both behavioral and biological markers. However, whether L-3,4-dihydroxyphenylalanine (L-dopa) influences these markers associated with circadian rhythm or not is still an open question. This study aims to explore the L-dopa effects on the rhythmic expression of core clock proteins [brain and muscle Arnt-like protein-1 (BMAL1) and circadian locomotor cycle kaput (CLOCK)], in the striatum of the rat model of PD and its underlying molecular mechanisms. Methods: Unilateral 6-hydroxydopamine (6-OHDA)-lesioned rat models were used in this study. L-dopa administrations were adopted to investigate the changes of circadian rhythm in PD. The behavioral tests and the measurements of the blood pressure (BP) and temperature were evaluated. The striatum was collected at intervals of 4 h. Western blot was used to examine the expressions of clock protein and the molecular protein of the D1R-ERK1/2-mTOR pathway. The rhythmic expressions of symptom parameters and circadian proteins were analyzed using the Cosinor model and/or the coefficient of variability (CV) that was used to describe the variability of the 24-h rhythm. Results: The circadian rhythms of BP and temperature were disrupted in 6-OHDA-lesioned PD rats compared with the sham group, while this process was reversed mildly by L-dopa treatment. The expressions of BMAL1 and CLOCK protein were rhythmic fluctuated without significant phase alterations when 6-OHDA or L-dopa was applied. Furthermore, the expressions of striatal BMAL1 protein in the 6-OHDA-lesioned group were significantly lower than those in the sham group at 04:00, 08:00, and 12:00, and the CLOCK protein was decreased at 04:00, 08:00, 12:00, 16:00, and 20:00 (all p < 0.05). The CV of the expressions of both BMAL1 and CLOCK was decreased in the 6-OHDA group; this process was reversed by L-dopa. Moreover, the CV of BMAL1 and CLOCK was elevated in the L-dopa rats. The phosphorylation levels of ERK1/2, S6K1, and 4E-BP1 in 6-OHDA-lesioned striatum were increased by L-dopa or D1 receptor agonist SKF38393 (p < 0.05, respectively), not by the combination of L-dopa and D1 receptor antagonist SCH23390, which was similar to the expressions of BMAL1 and CLOCK. Conclusion: L-dopa recovers the circadian rhythm disturbances in PD rats by regulating the D1R-ERK1/2-mTOR pathway.